2010
DOI: 10.1111/j.1475-6811.2010.01256.x
|View full text |Cite
|
Sign up to set email alerts
|

Attachment avoidance and the cultural fit hypothesis: A cross-cultural investigation

Abstract: This study examined the impact of attachment avoidance on relationship outcomes. A “cultural fit” hypothesis, which states that individual differences in personality should be associated with relationship problems if they encourage patterns of behavior that are incongruent with cultural norms, was investigated. It was hypothesized that attachment avoidance, a style of relationship in which emotional distance and independence are emphasized, would be more strongly associated with relationship problems in more c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
103
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(119 citation statements)
references
References 59 publications
15
103
1
Order By: Relevance
“…However, opposing the congruence discussed above, Friedman et al (2010) observed that the motivations behind anxiously attached individuals' preference for close relationships may be 'self-serving'. In other words, anxiously attached individuals may seek relationship closeness as an end in itself to satisfy the need for self-worth (Mikulincer and Shaver, 2007).…”
Section: Culture As a Moderator Of Interpersonal Justice Perceptionsmentioning
confidence: 43%
See 3 more Smart Citations
“…However, opposing the congruence discussed above, Friedman et al (2010) observed that the motivations behind anxiously attached individuals' preference for close relationships may be 'self-serving'. In other words, anxiously attached individuals may seek relationship closeness as an end in itself to satisfy the need for self-worth (Mikulincer and Shaver, 2007).…”
Section: Culture As a Moderator Of Interpersonal Justice Perceptionsmentioning
confidence: 43%
“…Initial evidence also suggests that attachment orientations may have consistent effects on relationship dynamics in contexts beyond the Western settings traditionally studied. For example, Friedman et al (2010) found that attachment insecurity predicted (romantic) relationship outcomes for individuals in culturally diverse nations (US, China and Mexico). Given this, we expect the basic associations between attachment orientations and interpersonal justice (i.e.…”
Section: Culture As a Moderator Of Interpersonal Justice Perceptionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among immigrants, however, the age-related increase in autonomy may be an indication of adaptation to the western individualistic culture represented by peers and school. In the often heritage-oriented collectivist family context, such as among immigrants from the former Soviet Union, being autonomous in adolescence might not meet the cultural expectations of the family (Kagitcibasi 2005;Love and Buriel 2007), and thus a cultural misfit might lead to heightened levels of depressive symptoms (Friedman et al 2010). …”
Section: Mother-adolescent Agreement and Psychosocial Outcomesmentioning
confidence: 99%